The Function of National Culture in Moderating Digital Marketing's Influence on Consumer Purchase Interest (Case Study on Tokopedia Users in Denpasar City) - rettobjaan, vitalia fina carla; Bagus Aristayudha, A.A. Ngurah (Universitas Ibn Khladun Bogor, 2023)
The purpose of this study is to ascertain how national culture influences the influence of digital marketing on customer purchasing interest. (Case Study of Tokopedia Users in Denpasar City). There are many elements that influence consumer buying interest, but some of them are rarely quantified, such as the impact of national culture on the use of digital marketing. This study uses a combination of methods. 106 respondents made up the study's quantitative sample, while 8 informants made up the study's qualitative sample. The smartPLS tool is used to assist in the data analysis for this investigation. The findings demonstrated that the impact of digital marketing had a favorable affect on consumer purchasing interest. The influence of national culture on consumer purchasing interest is beneficial.